KULINER BÉTUTU BALI SEBAGAI POTENSI WISATA EDUKASI DI SMK PGRI 1 BADUNG - I Made Yuniartha; I Wayan Wiwin; I Gusti Ngurah Pertu Agung (CV. ADIBA AISHA AMIRA, 2025)
This study was motivated by concerns about the erosion of traditional Balinese cuisine amid the dominance of modern and fast food, especially among the younger generation. The main issue raised in this study is how Balinese Bétutu culinary arts can be developed as educational tourism potential at SMK PGRI 1 Badung. The research questions include the form of learning, learning experiences that can be explored, a SWOT analysis of the potential, and preservation strategies. The objectives of this study are to identify the form of Balinese Bétutu culinary learning as a potential educational tourism attraction at SMK PGRI 1 Badung. To identify learning experiences that can be explored in Balinese Bétutu culinary learning as educational tourism potential at SMK PGRI 1 Badung, to analyse Balinese Bétutu culinary learning as educational tourism potential at SMK PGRI 1 Badung, and to determine preservation strategies for Balinese Bétutu culinary learning as educational tourism potential at SMK PGRI 1 Badung. This study employs a descriptive qualitative approach using Edgar Dale's Cone of Experience theory and Cooper et al.'s tourism potential theory. Data collection was conducted through participatory observation, unstructured interviews, and documentation. Data analysis was carried out through reduction, presentation, and verification stages. The researcher selected the location at SMK PGRI 1 Badung purposively because it was relevant to the topic and had culinary practice facilities that supported the research. The results of the study indicate that Bétutu culinary education at SMK PGRI 1 Badung not only provides students with technical cooking skills but also strengthens their understanding of local cultural values. Practical learning activities combined with an educational tourism approach create a holistic learning experience. A SWOT analysis identified strengths in the teaching methods and industry collaboration, as well as weaknesses in the form of limited raw materials and facilities. The proposed preservation strategies include strengthening teacher training, innovating the curriculum based on local wisdom, and developing a culinary tourism promotion network. This study is expected to serve as a foundation for developing a traditional culinary education model based on educational tourism that supports cultural preservation and vocational skill enhancement.